Ekspolasi Pengalaman dan Perwujudan Nilai-Nilai Akhlak Mulia dalam Perilaku Sosial Siswa Kelas V di SDN Purworejo 03: Studi Kasus Keteladanan Guru - Rahmawati, Selfi Dewi; Shanie, Arsan; Ya’la, Aida Nur Fatra; Fawaid, M.; Aini, Isfatul; Alhusaini, Rofi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study explores the application of noble moral values through teachers’ example and its impact on class V students’ social behavior in Purworejo SDN 03. Realizing the crucial role of education in character formation amid global challenges, this study aims to understand in depth how teachers act as role models and their influence on students’ behavior. Using a descriptive qualitative approach with a case study design, data were collected through non- participant observation, semi-structured interviews, and documentation. Study results indicate that teachers consistently implement the values of honesty, responsibility, courtesy, concern, and fairness, both in and out of the classroom. The majority of grade V students showed good social behavior, reflecting courtesy, responsibility, concern, and cooperation, although a minority still showed less positive behavior. These positive relationships are supported by strong leadership, collaboration among teachers, and the school’s character development program. The study concluded that teachers’ example is a highly effective method for character education, significantly shaping students’ social behavior.